Miniaturized droplet microarray platform enables maintenance of human induced pluripotent stem cell pluripotency. (September 2021) - Liu, Yanxi; Chakraborty, Shraddha; Direksilp, Chatrawee; Scheiger, Johannes M.; Popova, Anna A.; Levkin, Pavel A.
Abstract: The capacity of human induced pluripotent stem cells (hiPSCs) for indefinite self-renewal warrants their application in disease modeling, drug discovery, toxicity assays and efficacy screening. However, their poor proliferation ability, inability to adhere to surfaces without Matrigel coating and tendency to spontaneously differentiate in vitro hinder the application of hiPSCs in these fields. Here we study the ability to culture hiPSCs inside 200 ​nL droplets on the droplet microarray (DMA) platform. We demonstrate that (1) hiPSCs can attach to the Matrigel (MG)-free surface of DMA and show good viability after 24 h culture; (2) hiPSC do not spontaneously differentiate when cultured on the MG-free surface of DMAs; (3) culturing of hiPSCs in 200 ​nL as compared to 2 ​mL culture leads to higher expression of the Nanog pluripotency marker. Overall, the results demonstrate the possibility to culture undifferentiated hiPSCs in 200 ​nL droplets on DMA, thereby opening the possibility for high-throughput screenings of hiPSCs with various factors without compromising the results through the involvement of animal-derived materials, such as Matrigel. Graphical abstract: Image 1